Implementasi Smart Governance Di Indonesia 2025: Dari Model Birokratis Ke Sistem Berbasis Kecerdasan Buatan - Ni Nyoman Kartika Yanti; Ni Made Dwi Widari (Public Inspiration : Jurnal Administrasi Publik, 2026)
Smart governance plays an essential role in Indonesia’s digital transformation agenda. This study analyzes the development of smart governance from recent policy reforms, the establishment of GovTech Indonesia (INA Digital), and the growing use of artificial intelligence (AI) in public administration. Using a qualitative descriptive method, the research draws on government regulations, academic sources, and case examples to evaluate progress and ongoing challenges. The findings show that Indonesia has built a solid regulatory foundation and begun integrating thousands of government applications to improve service delivery. However, significant barriers remain, including unequal digital infrastructure, limited digital competence among civil servants, and fragmented data-sharing practices. At the same time, strategic collaborations with the private sector, interoperable systems such as INSW, and capacity-building programs—such as AI training for civil servants—offer promising opportunities to accelerate smart governance. This study highlights Indonesia’s gradual shift toward more integrated and AI-supported public services.